2016
DOI: 10.1016/j.jtv.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the performance of the Braden Q and the Glamorgan paediatric pressure ulcer risk assessment scales in general and intensive care paediatric and neonatal units

Abstract: AimsTo compare the predictive ability of two risk assessment scales used in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
0
13
1
2
Order By: Relevance
“…This study found that infants in the intermediate care units also developed PUs. Specifically, the cumulative incidence rate was 28.18% in NICU, a higher figure than in previous research studies . However, when considering the incidence in intermediate care units, the total figure was lower (12.70% vs 1.20%).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…This study found that infants in the intermediate care units also developed PUs. Specifically, the cumulative incidence rate was 28.18% in NICU, a higher figure than in previous research studies . However, when considering the incidence in intermediate care units, the total figure was lower (12.70% vs 1.20%).…”
Section: Discussioncontrasting
confidence: 49%
“…Specifically, the cumulative incidence rate was 28.18% in NICU, a higher figure than in previous research studies. 12,32 However, when considering the incidence in intermediate care units, the total figure was lower (12.70% vs 1.20%). The incidence 12 in the same terms.…”
Section: Epidemiology Of Pus In Neonatal Patientsmentioning
confidence: 95%
“…In Jordan, the prevalence of PU in generalized hospitalized patients was found to be 16%, with 44% of PU patients residing in intensive care units. [19] In addition, an incidence rate of 9% for pediatric ICU patients was reported in one university hospital, [27] and, in a separate study, 11 of 166 pediatric patients had developed 16 ulcers with a prevalence of 6.6%. Of these, 90% were observed in the ICUs.…”
Section: Discussionmentioning
confidence: 97%
“…In a performance comparison of these scales in children’s hospitals, the Glamorgan scale had the highest predictive ability [6] although comparison of the Braden Q and Glamorgan among pediatric inpatients has also concluded that either scale could be used [7]. Our literature review did not discover any risk assessment scales specifically validated for pediatric patients in the home setting although home health nursing literature has suggested that they could be used [8].…”
mentioning
confidence: 99%